Estudio de pertinencia de la carrera de Administración Pública de la Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López 2020-2021 - Cuzme Delgado, Jeniffer María (2022)
Relevance studies in university careers are used to analyze the quality of educational processes, the main objective of the research was to establish the relevance of the Public Administration major in relation to advances in science, technology, and professional training, in order to satisfy the needs and labor demands of the employers, methods such as inductive, deductive and analytical were applied within the three investigative stages, which allowed knowing the facts for their subsequent analysis, through the techniques used, results were obtained that allowed knowing the labor reality and the lack of occupational demand of the graduates in addition to their level of acceptance in different institutions, to finalize the investigation with the data obtained, an assessment matrix of relevance was made based on the principles established by the law in which it was determined that the major, if it meets partially, concluding that, in order to continue guaranteeing a desired professional profile, the curriculum must be constantly evaluated and, when necessary, a redesign of the career in a way that always allows the delivery of a quality professional profile and in accordance with labor competencies.